Supporting the Transition from Primary to Postprimary Education in 2021: Perspectives from Irish Postprimary Practitioners - Hilary O'Connor; Paul Flynn (MDPI AG, 2021)
The transition from primary to postprimary education is a significant milestone in children's education and can be characterised by the multiple challenges that they experience, specifically the move from childhood to adolescence, from one institutional context to another, and from established social groups into new social relations. This research employs a theoretical framework that describes this transition from the perspective of secondary school inservice practitioners as they aim to help students to make a successful transition. An incremental, sequential mixed-methods data collection strategy took the form of an exploratory survey followed by qualitative semistructured interviews. Current transition practices in the context of the challenges presented in Irish secondary schools are reported on in five key areas: administration, social and emotional supports, curriculum support, pedagogical support, and management/autonomy of learning. The findings of this research also highlight a need to reflect on the purpose and timing of current practices, along with calls for continuing professional development programmes to be developed that specifically target the challenges faced by Irish inservice teaching practitioners. It is hoped that this paper will spark discourse relating to the development of transitional supports for students and associated training for those who are best placed to provide those supports.